ANALYSIS OF TEACHERS AND STUDENTS NEEDS FOR THE DEVELOPMENT OF AI BASED INTERACTIVE E-MODULES IN ENHANCING ACADEMIC LITERACY: Analisis Kebutuhan Guru Dan Siswa Terhadap Pengembangan E-Modul Interaktif Berbasis Ai Dalam Meningkatkan Literasi Akademik - Seplianti, Angelina; Syarifuddin (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The advancement of digital technology, particularly artificial intelligence (AI), has opened new opportunities for developing more adaptive and personalized learning media. This study aims to analyze the needs of teachers and students regarding the development of an AI-based interactive e-module as a means to enhance academic literacy. A descriptive qualitative approach was used, employing questionnaires and semi-structured interviews with high school teachers and students. The results indicate that both teachers and students require learning tools capable of adapting to individual proficiency levels, providing real-time feedback, and facilitating key literacy skills such as reading comprehension, academic writing, and information evaluation. These findings suggest that AI-based interactive e-modules hold significant potential to address the limitations of conventional learning and support the achievement of academic competencies more effectively. This study serves as a foundational step in designing pedagogically relevant and technologically innovative e-modules